Effects of Prescribed Fire Timing on Native Plant Composition, Forage Biomass Accumulation, and Root Carbohydrate Reserves in the Kansas Flint Hills: Year 2 of 6 - Z. M. Duncan; A. J. Tajchman; M. P. Ramirez; J. Lemmon; W. R. Hollenbeck; D. A. Blasi; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective was to document the effects of prescribed fire timing on native plant composition, forage biomass, and root carbohydrate concentrations in key native tallgrass species in the Kansas Flint Hills. Study Description:This experiment was conducted at the Kansas State University Beef Stocker Unit. Eighteen pastures were grouped by watershed and assigned to one of three prescribed-burn treatments: spring (April 7 ± 2.1 days), summer (August 21 ± 5.7 days), or fall (October 2 ± 9.9 days). Botanical composition, forage biomass, and root carbohydrate concentrations in big bluestem, little bluestem, Indian grass, and purple prairie clover were evaluated annually. The Bottom Line:Data from the first two years of a six-year study were interpreted to indicate that basal cover of forage grasses and forbs, forage biomass accumulation, and root carbohydrate concentrations in key tallgrass species did not differ between prescribed-fire treatments.
Keywords: grazing; prescribed fire; sericea lespedeza